2019
DOI: 10.1159/000501692
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Uveal Melanoma Patients in Ireland: A Single-Centre Survey

Abstract: Background: Uveal melanoma and its treatment can influence the physical and psychological well-being of patients in a way that differs from other cancers. Factors influencing quality of life (QOL) include visual impairment, changes in appearance, day-to-day functioning, ocular discomfort, and worry regarding disease recurrence. Objective: We aimed to study both general and disease-specific QOL in uveal melanoma patients in Ireland and compare QOL between a plaque radiotherapy group and an enucleation treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(30 citation statements)
references
References 20 publications
0
30
0
Order By: Relevance
“…The total sample size of 35 studies was 13 018 (ranging from 30 to 2671), and the age of study subjects ranged from 14 to 73 years. Five studies did not report the age of study subjects 27,30,39,47,49 . With regard to FCR measurement tools, 14 studies did not report reliability and validity 15,18,24,26,29,30,32,39–41,46–49,51 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The total sample size of 35 studies was 13 018 (ranging from 30 to 2671), and the age of study subjects ranged from 14 to 73 years. Five studies did not report the age of study subjects 27,30,39,47,49 . With regard to FCR measurement tools, 14 studies did not report reliability and validity 15,18,24,26,29,30,32,39–41,46–49,51 .…”
Section: Resultsmentioning
confidence: 99%
“…The finding of studies did not reach a consistent conclusion about the correlation between FCR and RT. Twenty studies showed that no statistical significance existed between FCR and RT 15,18,19,24,26–29,33,36,38–40,42–44,47–50 . Two studies showed that receiving RT was a protective factor of FCR 21,45 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Summary tables including all correlation heatmaps, final multiple linear regression models and figures on marginal means are provided as an attachment to this article (Additional files 1, 2, 3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22.…”
Section: Statisticsmentioning
confidence: 99%
“…The QOL of patients after UM treatment has been investigated in numerous studies over the past few years, and different treatment methods have been compared [7][8][9][10][11][12][13][14][15]. However, studies on the pre-treatment QOL, with a focus on the treatment procedure, are rare.…”
Section: Introductionmentioning
confidence: 99%